2021
DOI: 10.3389/fimmu.2021.635903
|View full text |Cite
|
Sign up to set email alerts
|

AhR Ligands Differentially Regulate miRNA-132 Which Targets HMGB1 and to Control the Differentiation of Tregs and Th-17 Cells During Delayed-Type Hypersensitivity Response

Abstract: Aryl hydrocarbon receptor (AhR), is a transcription factor and an environmental sensor that has been shown to regulate T cell differentiation. Interestingly, AhR ligands exert varying effects from suppression to exacerbation of inflammation through induction of Tregs and Th-17 cells, respectively. In the current study, we investigated whether the differential effects of AhR ligands on T cell differentiation are mediated by miRNA during delayed-type hypersensitivity (DTH) reaction against methylated Bovine Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
(82 reference statements)
2
24
0
Order By: Relevance
“…inflammation associated with the DTH response. Our study demonstrated that AhR ligands, such as TCDD and FICZ, have opposite effects on DTH response mediated by mBSA, with the former suppressing DTH while the latter, enhancing this response, consistent with our recent studies (34). Interestingly, in our previous report (34) on mBSA-induced DTH response, we focused on T-cell responses in the draining popliteal lymph nodes while in the current study, because we were interested in studying gut-associated microbiota and inflammation, resorted to MLNs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…inflammation associated with the DTH response. Our study demonstrated that AhR ligands, such as TCDD and FICZ, have opposite effects on DTH response mediated by mBSA, with the former suppressing DTH while the latter, enhancing this response, consistent with our recent studies (34). Interestingly, in our previous report (34) on mBSA-induced DTH response, we focused on T-cell responses in the draining popliteal lymph nodes while in the current study, because we were interested in studying gut-associated microbiota and inflammation, resorted to MLNs.…”
Section: Discussionsupporting
confidence: 93%
“…Our study demonstrated that AhR ligands, such as TCDD and FICZ, have opposite effects on DTH response mediated by mBSA, with the former suppressing DTH while the latter, enhancing this response, consistent with our recent studies (34). Interestingly, in our previous report (34) on mBSA-induced DTH response, we focused on T-cell responses in the draining popliteal lymph nodes while in the current study, because we were interested in studying gut-associated microbiota and inflammation, resorted to MLNs. Thus, we were surprised to note that the changes brought about by AhR ligands in the MLNs were similar to that seen in the draining lymph nodes (34) in that TCDD caused induction of Tregs while suppressing Th17 cells, whereas FICZ had the opposite effects on these T cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations